Transformasi Koperasi Menuju Era Society 5.0 dalam Meningkatkan Perekonomian Indonesia - Ival Fadliyanto (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
The development of digital technology has brought significant changes to various economic sectors, including cooperatives as one of the pillars of the people’s economy in Indonesia. Cooperatives, which have long been known for their principles of mutual cooperation and shared welfare, are required to adapt to technological developments in the Society 5.0 era. This study aims to analyze the opportunities, challenges, and strategies for cooperative transformation toward the digital era in order to improve their competitiveness and contribution to the national economy. The research method used is a qualitative method with a descriptive approach through a literature study of various journals, scientific articles, and reliable sources related to cooperative digitalization and Society 5.0. The results of the study indicate that digital transformation can help cooperatives improve operational efficiency, expand market access, enhance member service systems, and create transparency in financial management. However, the transformation process still faces various obstacles, such as low digital literacy, limited technological infrastructure, lack of funding, and resistance to change. Therefore, an integrated strategy is needed through improving digital literacy, strengthening cooperation with the government and private sector, developing digital business models, and providing regulatory support that promotes cooperative transformation in the Society 5.0 era.